Living with Dementia in Aotearoa (LiDiA): a cross-sectional feasibility study protocol for a multiethnic dementia prevalence study in Aotearoa/New Zealand. Issue 5 (3rd May 2021) - Martinez-Ruiz, Adrian; Yates, Susan; Cheung, Gary; Dudley, Makarena; Krishnamurthi, Rita; Fa'alau, Fuafiva; Roberts, Mary; Taufa, Seini; Fa'alili-Fidow, Jacinta; Rivera-Rodriguez, Claudia; Kautoke, Staverton; Ma'u, Etuini; et al.
Abstract : Introduction: Aotearoa/New Zealand (NZ) is officially recognised as a bicultural country composed of Māori and non-Māori. Recent estimations have projected a threefold increase in dementia prevalence in NZ by 2050, with the greatest increase in non-NZ–Europeans. The NZ government will need to develop policies and plan services to meet the demands of the rapid rise in dementia cases. However, to date, there are no national data on dementia prevalence and overseas data are used to estimate the NZ dementia statistics. The overall aim of the Living with Dementia in Aotearoa study was to prepare the groundwork for a large full-scale NZ dementia prevalence study. Methods and analysis: The study has two phases. In phase I, we will adapt and translate the 10/66 dementia assessment protocol to be administered in Māori, Samoan, Tongan and Fijian–Indian elders. The diagnostic accuracy of the adapted 10/66 protocol will be tested in older people from these ethnic backgrounds who were assessed for dementia at a local memory service. In phase II, we will address the feasibility issues of conducting a population-based prevalence study by applying the adapted 10/66 protocol in South Auckland and will include NZ–European, Māori, Samoan, Tongan, Chinese and Fijian–Indian participants. The feasibility issues to be explored are as follows: (1) how do we sample to ensure we get accurate community representation? (2) how do we prepare a workforce to conduct the fieldwork and develop quality control? (3) how do we raise awareness of the study in the community to maximise recruitment? (4) how do we conduct door knocking to maximise recruitment? (5) how do we retain those we have recruited to remain in the study? (6) what is the acceptability of study recruitment and the 10/66 assessment process in different ethnic groups? Ethics and dissemination: The validity and feasibility studies were approved by the New Zealand Northern A Health and Disability Ethics Committee (numbers 17NTA234 and 18NTA176, respectively). The findings will be disseminated through peer-reviewed academic journals, national and international conferences, and public events. Data will be available on reasonable request from the corresponding author.